Analisis Reduksi Emisi Gas Kendaraan Bermotor Menggunakan Adsorben Berbasis Biomassa Limbah Tempurung Siwalan - Abdillah, Riko Ferdinand; Jawwad, Muhammad Abdus Salam (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Incomplete combustion of fossil fuels resulting from motor vehicle emissions releases hazardous pollutants such as carbon monoxide (CO) and hydrocarbons (HC). The high levels of these gases in emissions pose a significant threat to public health, creating an urgent need to develop and implement highly efficient processing or reduction technologies to ensure exhaust gas emission parameters remain within safe limits. This study demonstrates that activated carbon derived from siwalan (lontar) shell, specifically after activation with 25% Na2CO3 is highly effective in lowering exhaust gas emission levels, with the greatest reduction achieved using the largest adsorbent mass of 100 grams. The effectiveness of this adsorption is further supported by the statistical results of the Two-Way ANOVA model, which confirmed a significant influence of both adsorbent mass and adsorption process time. Consequently, the use of activated carbon from siwalan shell proves to be an effective and efficient solution for mitigating motor vehicle gas pollution. It holds significant potential for use as an emission reduction tool, particularly for older motor vehicles that lack existing emission control devices, and serves as a vital effort to comply with government regulations aimed at maintaining stable ambient air quality.